2015
DOI: 10.3233/jnd-150109
|View full text |Cite
|
Sign up to set email alerts
|

Exon 32 Skipping of Dysferlin Rescues Membrane Repair in Patients’ Cells

Abstract: Dysferlinopathies are a family of disabling muscular dystrophies with LGMD2B and Miyoshi myopathy as the main phenotypes. They are associated with molecular defects in DYSF, which encodes dysferlin, a key player in sarcolemmal homeostasis. Previous investigations have suggested that exon skipping may be a promising therapy for a subset of patients with dysferlinopathies. Such an approach aims to rescue functional proteins when targeting modular proteins and specific tissues.We sought to evaluate the dysferlin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 46 publications
1
24
0
2
Order By: Relevance
“…Not all NMDs will be amenable to NHEJ-mediated gene editing. Based on successful exon skipping studies in limb girdle muscular dystrophies (LGMD) 2B and C (due to mutations in dysferlin or gamma-sarcoglycan respectively) (1,12,73,134), it has been suggested that CRISPR could be used to generate functional proteins by NHEJ. Other NMDs caused by aberrant expression of toxic proteins, such as facioscapulohumeral muscular dystrophy (FSHD), could also in theory be targeted by NHEJ.…”
Section: Nhej For Other Nmdsmentioning
confidence: 99%
“…Not all NMDs will be amenable to NHEJ-mediated gene editing. Based on successful exon skipping studies in limb girdle muscular dystrophies (LGMD) 2B and C (due to mutations in dysferlin or gamma-sarcoglycan respectively) (1,12,73,134), it has been suggested that CRISPR could be used to generate functional proteins by NHEJ. Other NMDs caused by aberrant expression of toxic proteins, such as facioscapulohumeral muscular dystrophy (FSHD), could also in theory be targeted by NHEJ.…”
Section: Nhej For Other Nmdsmentioning
confidence: 99%
“… 28 Exon-skipping progress in dysferlinopathy has been limited to the in vitro skipping of DYSF exon 32 in human dysferlinopathy patient cells. 29 To date, no other therapeutic exon-skipping targets have been identified for dysferlinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Antisense oligonucleotide (AON)-based splice-switching approaches have been developed for therapeutic use in human for Duchenne muscular dystrophy (DMD), spinal muscular atrophy, 15 , 16 , 17 , 18 , 19 , 20 and dysferlinopathy. 21 , 22 However, splice-modulating efficiency remains low in humans, and AONs must be repeatedly applied throughout life using invasive injection protocols, spurring research for more efficient and less invasive strategies. The U7 small nuclear RNA (snRNA)-encoded antisense RNAs differ from DNA-analog based AONs, in that they can easily be packaged into a suitable viral vector (i.e., recombinant adeno-associated virus [rAAV]) to transduce a wide variety of tissues, including skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%